2001
DOI: 10.1182/blood.v97.11.3466
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 is a selective inducer of interleukin-12 p40 (IL-12p40) production and an inhibitor of bioactive IL-12p70 heterodimer

Abstract: Interleukin-12 p70 (IL-12p70) heterodimer, composed of p35 and p40 subunits, is a major Th1-driving cytokine, promoting cell-mediated immunity. In contrast, IL12p40 homodimer, secreted by APC in the absence of p35 expression, and free p40 monomer do not mediate IL-12 activity but act as IL-12 antagonists. Here it is reported that prostaglandin E 2 (PGE 2 ), an inflammatory mediator with a previously known Th2-driving function, dose-dependently enhances the IL-12p40 mRNA expression and the secretion of IL-12p40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
250
5
5

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(276 citation statements)
references
References 40 publications
16
250
5
5
Order By: Relevance
“…Interestingly, it has been shown previously that stimulation of DC with TNF-a and PGE 2 leads to a selective induction of p40 transcription and secretion while inhibiting p70 secretion. 2 The responsible mechanisms may be unique to IL-12 in that p40 can be secreted in several ways, as p40 monomer, p40-p40 homodimer, IL-12p70 and, if p40 is bound to p19, IL-23. This phenomenon has yet to be elucidated, but may involve the different kinetics of transcription of p40 and p35, different kinetics in the translation and post-translational modification, as well as the yet unknown influence of p19 as a competing binding partner for p40.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it has been shown previously that stimulation of DC with TNF-a and PGE 2 leads to a selective induction of p40 transcription and secretion while inhibiting p70 secretion. 2 The responsible mechanisms may be unique to IL-12 in that p40 can be secreted in several ways, as p40 monomer, p40-p40 homodimer, IL-12p70 and, if p40 is bound to p19, IL-23. This phenomenon has yet to be elucidated, but may involve the different kinetics of transcription of p40 and p35, different kinetics in the translation and post-translational modification, as well as the yet unknown influence of p19 as a competing binding partner for p40.…”
Section: Resultsmentioning
confidence: 99%
“…1 These chains are encoded by genes on different chromosomes and their production can be regulated independently. 2,3 IL-12 is produced by a number of cell types, including macrophages, neutrophilic granulocytes and dendritic cells (DCs). DCs may be the most important source of IL-12.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that the Th2-cell promoting mediator PGE 2 induces the secretion of IL-12p40 in DCs thereby inhibiting the production of the Th1-cell driving cytokine IL12p70 [16][17][18]. It has been proposed that blocking or washing out IL-12p70 production is sufficient to drive the differentiation of Th2-cell responses by the so-called default or exhaustion pathway [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…These include costimulatory molecules such as OX40 [12], ICOS-L [13], the Notch family member Jagged-2 [14], the cytokine IL-6 [15], or arachidonic acid metabolites such as PGE 2 [16][17][18]. Much less is known about the factors that induce such Th2-instructing DC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation